Auction design for a strategic reserve market for generation adequacy: On the incentives under different auction scoring rules - Gert Brunekreeft; Roland Meyer; Margarethe Rammerstorfer (Jacobs University Bremen, Bremen Energy Research (BER), 2013)
How should we select winning bids of generation units for strategic reserves that consist of capacity bids and energy bids? In this paper, we analyze two selecting mechanisms (scoring rules): "simultaneous" and "sequential". In case of a simultaneous scoring rule, capacity and energy bids are weighted and combined to a single score based on which the cheapest bids are selected. Under sequential scoring rule the selection depends solely on capacity bids. In both cases the energy bids are used to form the merit order for dispatch. We find that the main difference between the simultaneous and sequential scoring mechanism is that under sequential scoring the bids are biased towards lower capacity bids and higher energy bids, since it is only the capacity part that "opens the door" to the reserve market. We find that a simultaneous scoring is favorable from a welfare perspective, since it avoids the strategic incentives for excessive mark-ups on energy costs and limits the incentives for collusive behavior. This reduces the risk of inefficient selection and dispatch of reserve units compared to a sequential scoring mechanism.
Keywords: D47; D44; L94; 330; Electricity; generation adequacy; market design; auction design; reserve market